(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: People died due to liver cirrhosis caused by alcohol consumption across India. Evidence shows many and more alcoholrelateddeaths Major crimes and accidents are because of alcohol, which also cause to robberies sexual harassment.Aim: To assess the Quality of Life among Alcoholic Patient Method and material: Non experimental design with Descriptive researchapproach used for the study. The study was conducted in De-addiction Centre Pune, Maharashtra, India. Non-probability convenientsampling technique was used for selecting 50 Alcoholic patient. The data was collected, organize in table form and analyzed based onobjectives of the study using descriptive and inferential statistics.Result: Maximum 40% had 30 to 40 years,34% patients had up to 30 years, 20% patients had 40 to 50 years of age group majority68% alcoholic patient are stay in urban area and 32% are stay in rural area. In present study we found that there is having associationbetween age and monthly income with factors like physical, psychological, social, environment. We found that there were no anyassociation between age and physical factorConclusion: The study confirms the quality of life of alcoholic patient is lower and physical, psychological, social, environmentalfactors is affecting the quality of life of alcoholic patient.